Accuracy of McMurray's test, modified version and joint line tenderness in diagnosing chronic meniscus tear in knee joint - Choon, Teh Wai (2017)
Introduction: “Special clinical test” played an important role in physical examination and are thought to diagnose meniscus injury. Among those special tests, original McMurray’s test, modified version of McMurray, and joint line tenderness (JLT) are commonly used in practice. There were only limited literatures that take into consideration of the injury time of the meniscus for the diagnostic accuracy of such clinical test. Therefore, in chronic meniscus injury the diagnostic accuracy of those special tests were unclear and questionable. Material & Method: This is a cross sectional study and 50 patients enrolled from January 2016 till June 2017. The inclusion criteria were patients had duration injury of more than 6 month, at least 16 years old or older and underwent knee arthroscopic surgery. All patients underwent physical examination first then schedule for arthroscopy performed by the same surgeon. 5 statistical parameters were calculated based on the formula: accuracy (%), sensitivity (%), specificity (%), positive predictive value (PPV %) and Negative predictive value (NPV %). Results: The mean age was 25.7 years ranging from 16 to 44 years old (SD 6.8 years). Modified version Mc-Murray test showed the highest sensitivity for both medial lesion (36.36%) and lateral lesion (35.29%). It also had highest NPV (64.10% -medial and 73.17%- lateral) and highest PPV (72.73%-medial and 66.67%-lateral). It also had highest accuracy at 66% (medial) and 72% (lateral). Original Mc-Murray test showed lowest sensitivity for lateral lesion (18.75%) however highest specificity for both lesion (92.59%-medial and 91.18%-lateral). JLT showed lowest specificity at 89.29% (medial) and 87.88% (lateral). It also showed lowest accuracy for medial lesion (60%) and same accuracy with Original Mc- Murray test at 68% for lateral lesion.Conclusion: The results indicate that Original McMurray’s test, Modified version and JLT have overall low sensitivity and high specificity in diagnosing chronic meniscal tear. It also highlights that Modified versions Mc-Murray test had highest accuracy than the original Mc- Murray test and JLT. However in clinical practice, those special tests should not standalone, but should use in combination for better accurate diagnosing chronic meniscus tear.